Search for four-top-quark production in the single-lepton and opposite-sign dilepton final states in pp collisions at √s=13TeV with the ATLAS detector - Aaboud, Morad; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Kugel, Andreas; Napolitano, Fabrizio; S̜ahinsoy, Merve; et al. (Physical review, 2019)
A search for four-top-quark production, $t\bar{t}t\bar{t}$, is presented. It is based on proton-proton collision data with a center-of-mass energy $\sqrt{s}$ = 13 TeV collected by the ATLAS detector at the Large Hadron Collider during the year 2015 and 2016, corresponding to an integrated luminosity of $36.1$ fb$^{-1}$. Data are analyzed in both the single-lepton and opposite-sign dilepton channels, characterized by the presence of one or two isolated electrons or muons with high-transverse momentum and multiple jets. A data-driven method is used to estimate the dominant background from top-quark pair production in association with jets. No significant excess above the Standard Model expectation is observed. The result is combined with the previous same-sign dilepton and multilepton searches carried out by ATLAS and an observed (expected) upper limit of 5.3 (2.1) times the four-top-quark Standard Model cross section is obtained at 95% confidence level. Additionally, upper limit on anomalous four-top-quark production cross section is set in the context of an effective field theory model. A search for four-top-quark production, tt¯tt¯, is presented. It is based on proton-proton collision data with a center-of-mass energy s=13 TeV collected by the ATLAS detector at the Large Hadron Collider during the years 2015 and 2016, corresponding to an integrated luminosity of 36.1 fb-1. Data are analyzed in both the single-lepton and opposite-sign dilepton channels, characterized by the presence of one or two isolated electrons or muons with high-transverse momentum and multiple jets. A data-driven method is used to estimate the dominant background from top-quark pair production in association with jets. No significant excess above the Standard Model expectation is observed. The result is combined with the previous same-sign dilepton and multilepton searches carried out by the ATLAS Collaboration and an observed (expected) upper limit of 5.3 (2.1) times the four-top-quark Standard Model cross section is obtained at 95% confidence level. Additionally, an upper limit on the anomalous four-top-quark production cross section is set in the context of an effective field theory model.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The ATLAS Collaboration: M. Aaboud, V.Andrei, C. Antel, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, J. Jongmanns, A. Kugel, F. Napolitano, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, D. Sosa, T.M. Spieker, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels, X. Yue [und weitere]
Gesehen am 10.12.2020